Factors Assisting Social Workers in Empowering People with an Intellectual Disability In Social Day Care Centres: A Socioeducational Aspect - Raudeliūnaitė, Rita; Gudžinskienė, Vida (Special Education, 2023)
Socioeducational services, which are provided in day care centres, have a substantial impact on the empowerment of people with an intellectual disability. The article reveals factors, which assist social workers in empowering people with an intellectual disability in day care centres. Qualitative research was chosen for the study while using the method of a semi-structured interview. Eight social workers, who work with people with an intellectual disability in day care centres were chosen for the research. The obtained data were analysed by using the method of a qualitative content analysis while adhering to inductive logic of classifying into categories, which is based on the study data. The study revealed factors assisting in empowering people with an intellectual disability in social care centres: a positive attitude towards a person with an intellectual disability, respect for the opinion of a person when taking decisions related to him/her, the preparation, implementation and assessment of an individual plan when responding to individual personal needs, the creation of physical, informational and communicational environment increasing personal activeness and independence, the creation and maintenance of a favourable psychosocial environment in the community of a day care centre, the involvement of day centre attendees in the institution’s decision-making at various levels, the development, maintenance and expansion of personal competences, which increase their independence. A positive attitude towards a person with an intellectual disability should be associated with non-concentration on a disability, but the perception of a person through the lenses of his abilities, strengths, and not the lenses of his/her inability and weaknesses, the acknowledgement of personal individuality and his/her possibilities and the discernment of opportunities in the arising difficulties, as well as a partnership in relationships between an employee and a recipient of services. Respect for the opinion of a person when taking decisions related to him/her should be associated both with an opportunity for a person to express his opinion when decisions, which are related to him/her, are taken and the obtaining and supply of information from a person through the means empowering him/her to participate while taking decisions and by providing a person with an intellectual disability with adjuster, but not substitutionary assistance. When preparing, implementing and assessing an individual plan of a person it is important to know a person and his/her immediate environment, to identify strengths and resources both in a person, his/her immediate environment and a community and to use them in the empowerment process. In addition, it is important to cooperate with a person with an intellectual disability and his/her close relatives when preparing, implementing and assessing an individual plan. When empowering persons with an intellectual disability the creation of physical, information and communication environment, the use of alternative means, as well as those facilitating communication are important. The creation of a favourable psychoactive environment in the community of a day care centre while developing and maintaining positive relationships both between day care employees and attendees and the attendees of a centre themselves is equally important. The involvement of the attendees of a day care centre in decision-making at various levels of an institution is attributable to the involvement of them in decision-making related to daily activities, tasks in them, the self-government of an institution, as well as the assumption and implementation of responsibilities and obligations and their involvement in the assessment of service quality. The maintenance and expansion of personal competences increasing independence are important empowerment factors to persons with an intellectual disability relatable to the maintenance and expansion of domestic, health friendly, social and work skills and personal involvement in sociocultural activities. Furthermore, when developing and maintaining competences in persons with an intellectual disability, which increase their independence, the social worker has to be patient in order to achieve a result and not to give in to despair, if he/she fails to achieve it. When working with persons with an intellectual disability an empowerment process, but not a result is important.